Evaluation of The Effect of Airline Employees' Social Intelligence on Individual-Organization Adaptation and Job Satisfaction (Third Sector Social Economic Review, 2025)
The aim of this study is to examine the effect of social intelligence on person–organization fit and job satisfaction among airline employees working in ground services. A quantitative research design was adopted and data were collected by means of a structured questionnaire. The population of the study consists of employees working in airport ground services. Using convenience sampling, 420 questionnaires were distributed and, after excluding incomplete or incorrectly filled forms, 386 usable responses were obtained. The data were analyzed with SPSS 24.0 using frequency analyses, reliability and factor analyses, correlation analysis and multiple regression analysis.The findings indicate that social intelligence has a positive and significant effect on both person–organization fit and job satisfaction. Regarding the sub-dimensions of social intelligence, social information processing and social awareness significantly predict person–organization fit, whereas the effect of social skills is not statistically significant. In terms of job satisfaction, social skills and social awareness have positive and significant effects, while social information processing does not significantly predict job satisfaction. Overall, the results suggest that social intelligence – particularly the social awareness dimension – is a critical personal competence for enhancing organizational fit and job satisfaction of employees in the aviation sector.